2021
DOI: 10.3390/cancers13112800
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Analysis of the Impact of Radiotherapy on Immunotherapy Efficacy in Non-Small Cell Lung Cancer

Abstract: Background: Immunotherapy (IO) provides a significant benefit for a subgroup of non-small cell lung cancer (NSCLC) patients. Radiotherapy (XRT) might enhance the efficacy of IO. We evaluated the impact of the specifics of XRT treatments on the OS of IO-treated NSCLC patients. Methods: Metastatic NSCLC patients treated with IO were retrospectively identified. Parameters included demographics, tumor characteristics, IO and XRT details. Correlation between the parameters and OS was tested with Cox regression. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…More than half of the studies were reported from the Far East (n = 15) (Ichiki et al, 2019;Jiang et al, 2020;Kitadai et al, 2020;Takada et al, 2020;Ke et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Pu et al, 2021;Sato et al, 2021;Tokuyama et al, 2021;Chen et al, 2022;Kim et al, 2022;Li et al, 2022;Wu et al, 2022;Zhang et al, 2022), followed by Europe (n = 12) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Cantini et al, 2020;Awada et al, 2021;Onn et al, 2021;Ruiz-Bañobre et al, 2021;Stares et al, 2021;Assié et al, 2022;Schneider et al, 2022;Stares et al, 2022). A 3.5 gr/dL albumin cut-off was most frequently used in the included studies (n = 20) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the studies were reported from the Far East (n = 15) (Ichiki et al, 2019;Jiang et al, 2020;Kitadai et al, 2020;Takada et al, 2020;Ke et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Pu et al, 2021;Sato et al, 2021;Tokuyama et al, 2021;Chen et al, 2022;Kim et al, 2022;Li et al, 2022;Wu et al, 2022;Zhang et al, 2022), followed by Europe (n = 12) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Cantini et al, 2020;Awada et al, 2021;Onn et al, 2021;Ruiz-Bañobre et al, 2021;Stares et al, 2021;Assié et al, 2022;Schneider et al, 2022;Stares et al, 2022). A 3.5 gr/dL albumin cut-off was most frequently used in the included studies (n = 20) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thirty-four studies were included in the analyses for OS (Stroup et al, 2000;Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Ichiki et al, 2019;Cantini et al, 2020;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Swami et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;de Kouchkovsky et al, 2021;Ke et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;Pu et al, 2021;Ruiz-Bañobre et al, 2021;Sato et al, 2021;Stares et al, 2021;Tokuyama et al, 2021;Abuhelwa et al, 2022;Assié et al, 2022;Chen et al, 2022;Guo et al, 2022;Kim et al, 2022;Li et al, 2022;Stares et al, 2022;Wu et al, 2022;Yoo et al, 2022). In the meta-analysis, patients with lower albumin levels had a significantly increased risk of death (HR: 1.65, 95% CI: 1.52-1.80, p < 0.0001) than patients with higher albumin levels (Figure 1).…”
Section: The Association Between Hypoalbuminemia and Overall Survivalmentioning
confidence: 99%
“…A recent pan-cancer study with 1,714 patients has shown that hypoalbuminemia predicts poor survival upon ICI treatment, but this work lacked a melanoma-speci c analysis placing these associations into the context of other melanoma-speci c biomarkers (14). Multiple studies on NSCLC showed that hypoalbuminemia was associated with poor survival after immunotherapy, which held in a multivariate analysis adjusting for treatment line, prior radiotherapy, NLR, and ECOG PS (39,40). Another study comparing several laboratory and clinical factors in metastatic melanoma reported that albumin was an independent predictor for immunotherapy response after adjustment for LDH, CRP, NLR, brain metastasis, sex, and age (41,42).…”
Section: Discussionmentioning
confidence: 97%